If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 6 = 266 Reorder the terms: 6 + 8x = 266 Solving 6 + 8x = 266 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 8x = 266 + -6 Combine like terms: 6 + -6 = 0 0 + 8x = 266 + -6 8x = 266 + -6 Combine like terms: 266 + -6 = 260 8x = 260 Divide each side by '8'. x = 32.5 Simplifying x = 32.5
| 8-4(7x-2)=-11 | | 10(2x+1)=14(x+2) | | (-22)/(x+4)=-11/x | | 6x+4(-1)=-10 | | 2.6(1.4)=2.4(x) | | (7+3n^6+8n^4)+(6n^6-5n^4+8)= | | 10(x)=14(4) | | 42(28)=21(x) | | 9x+14=-4+3x | | 9(x)=4(15) | | 1=2k+9 | | x(9)=4(15) | | 2+54-5= | | -15=6f-3 | | 4x+8(-2)=-24 | | 3(x+4)=5x+4 | | 9x^2+16y^2=14400 | | 81=-8x-15 | | 16=(4-X)2 | | 6[3-(-8x-4)]=336x-186 | | q=250q-4q^2 | | 10(X+20)=300 | | mbq=250q-4q^2 | | .029x+.3=.0309x+.2 | | -2x^2=6x-1 | | x^3+13x=10x | | (.029x)+.3=(.0309x)+.2 | | 25+3b=5(b+3) | | 2x^2-13x=15 | | 25+3b=(b+3) | | 7+2x-5-x=-21 | | 25+3b=15b |